The significance of language knowledge on the labour market - Horváth-Csikós, Gabriella (Studia Mundi – Economica, 2018)
Globalization, internalization, the increasing number of learning and career opportunities and the demand for work satisfaction lead to the necessity of foreign language knowledge as foreign languages are inevitably essential on the present day labour market for information and knowledge transfer. The present paper seeks answer for the question whether foreign language knowledge can be the key to success on the labour market.